2021
DOI: 10.1055/s-0041-1730304
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiotherapy versus Surgery for the Treatment of Verrucous Carcinoma of the Larynx: A National Cancer Database Study

Abstract: Introduction Traditionally, larger lesions of laryngeal verrucous carcinoma are treated with surgical excision, with definitive radiotherapy generally reserved for smaller lesions. However, data utilizing modern databases is limited. Objective The authors sought to assess, utilizing the National Cancer Database, whether overall survival for patients with laryngeal verrucous carcinoma was equivalent when treated with definitive radiotherapy versus definitive surgery. Methods A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The resulting 5-year DSS, overall survival (OS) and laryngeal preservation rates of 87%, 97% and 81%, respectively, suggest that effective (limited) salvage surgery is still possible after unsuccessful radiotherapy. This is supported by large population studies that have found no differences in DSS and OS between those treated with primary surgery or primary radiotherapy, at least in patients with early-stage LVSCC [ 5 , 9 ]. Obviously, surgical salvage after unsuccessful radiotherapy could contribute significantly to achieving very high cure rates for these tumors.…”
Section: Treatment Optionsmentioning
confidence: 77%
“…The resulting 5-year DSS, overall survival (OS) and laryngeal preservation rates of 87%, 97% and 81%, respectively, suggest that effective (limited) salvage surgery is still possible after unsuccessful radiotherapy. This is supported by large population studies that have found no differences in DSS and OS between those treated with primary surgery or primary radiotherapy, at least in patients with early-stage LVSCC [ 5 , 9 ]. Obviously, surgical salvage after unsuccessful radiotherapy could contribute significantly to achieving very high cure rates for these tumors.…”
Section: Treatment Optionsmentioning
confidence: 77%
“…The controversy regarding the role of radiotherapy persists within two recent studies [48 ▪ ,49]. Based on a national cancer database, Kompelli et al reported that overall survival may be equivalent for patients with cT1 and cT2 LVC treated with primary radiotherapy compared with those treated by primary surgery [49].…”
Section: Treatment and Survivalmentioning
confidence: 99%
“…The controversy regarding the role of radiotherapy persists within two recent studies [48 ▪ ,49]. Based on a national cancer database, Kompelli et al reported that overall survival may be equivalent for patients with cT1 and cT2 LVC treated with primary radiotherapy compared with those treated by primary surgery [49]. In the same vein, Takenaka et al reported from the SEER database that the 5-year overall survival rates in the radiation and surgery groups were 72.7 and 72%, respectively.…”
Section: Treatment and Survivalmentioning
confidence: 99%
“…Surgery has long time been considered as the treatment of choice with overall survival and disease-free survival rates ranging from 86.8 to 100% [ 2 , 3 , 5 ]. The overall survival (OS) and disease-free survival (DFS) of radiotherapy were both lower than surgery with up to 70% of patients with disease free at follow-up [ 2 , 3 , 6 , 7 ]. The radiotherapy was moreover controversial regarding the potential risk of anaplastic transformation after treatment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The radiotherapy was moreover controversial regarding the potential risk of anaplastic transformation after treatment [ 8 ]. The discussions about the most effective treatment continue regarding recent studies supporting the usefulness of radiation approaches for the treatment of LVC [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%